2003
DOI: 10.1177/153331750301800410
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine as a treatment of neuropsychiatric disorders of Alzheimer's disease and other dementias: A 24-month follow-up of 68 patients

Abstract: Although the core feature of all types of dementia is progressive cognitive disruption, most demented patients also express noncognitive behavioral problems. These noncognitive problems lead to potentially devastating disabilities, and are often a major cause of stress, anxiety and concern for caregivers. Psychotropic drugs are frequently used to control these symptoms, but they have the potential for significant side effects, such as sedation, disinhibition, depression, falls, incontinence, parkinsonisms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 26 publications
1
46
0
4
Order By: Relevance
“…Pharmacological interventions used for FTD are based on neurotransmitter replacement strategies. Anecdotal reports and a number of small, and uncontrolled studies have shown that treatment with antidepressants (Chow and Mendez, 2002) or atypical antipsychotics (Moretti et al, 2003b) can be associated with improvement of behavioral symptoms. Moretti et al (2004) showed a decrease of behavioral disturbance by rivastigmine, demonstrated by a significant reduction of the NPI total score between baseline and final visit after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological interventions used for FTD are based on neurotransmitter replacement strategies. Anecdotal reports and a number of small, and uncontrolled studies have shown that treatment with antidepressants (Chow and Mendez, 2002) or atypical antipsychotics (Moretti et al, 2003b) can be associated with improvement of behavioral symptoms. Moretti et al (2004) showed a decrease of behavioral disturbance by rivastigmine, demonstrated by a significant reduction of the NPI total score between baseline and final visit after 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…59 The mechanism with which these medications reduce agitation is not fully understood. A case report 60 with risperidone and an open-label uncontrolled study 61 of olanzapine support the use of these medications in FTD. The reduction in the NPI observed with olanzapine treatment was similar in magnitude to that observed with antidepressant treatment (see table E-2).…”
Section: Treatment Reviewmentioning
confidence: 99%
“…The literature describes one case treated with risperidone 90 and an open trial with olanzapine that favours use of the drug. 91 Other dopaminergic agents, such as selegiline (IMAO-B), 92 have been used successfully to reduce neuropsychiatric symptoms. Methylphenidate has also been tested in patients with bvFTD with satisfactory results.…”
Section: Treatmentmentioning
confidence: 99%